GAS5 silencing attenuates hypoxia‐induced cardiomyocytes injury by targeting miR‐21/PTEN - Qianli Wang; Zan Xie (Immunity, Inflammation and Disease, 2023)
Abstract Introduction Myocardial hypoxia is an important factor causing myocardial infarction (MI). Interestingly, many unknown factors in the molecular mechanism of MI remain unclear. Our study explored the role of lncRNA growth arrest‐specific 5 (GAS5) in cell injury under hypoxia. Methods AS5 expression was assessed in MI and human cardiomyocytes under hypoxia through RT‐qPCR assay. Methyl thiazolyl tetrazolium assay, flow cytometry assay, and transwell assay was carried out for cell viability, cell apoptosis, cell migration, and invasion, respectively. The regulatory target of GAS5 was explored through a dual‐luciferase reporter assay. Results Our findings indicated that the upregulation of GAS5 was related to hypoxia. Downregulation of GAS5 expression could decrease hypoxia‐induced cell apoptosis and increase cell migration and invasion. Moreover, GAS 5 targeted miR‐21, which regulated the phosphatase and tension homology deleted on chromosome ten gene (PTEN) expression. Furthermore, the knockdown of miR‐21 eliminated the effect of GAS5 silencing on cell injury. Conclusion These results indicated that lncRNA GAS5 silencing decreased cardiomyocyte injury by hypoxia‐induced through regulating miR‐21/PTEN.